Comparison between Diclofenac Sodium and Ketorolac in the Management of Post-Appendectomy Pain - Nuzhat Jahan, Muhammad Jalil Malik, Muhammad Imran, Muhammad Waseem Anwar, Shahid Munir, Ibrahim Zafar Gondal, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare the Diclofenac Sodium and ketorolac in the management of post-appendectomy pain. Study design: Single blinded analytical comparative trial Place and duration of study: Tertiary Care Hospital, Lahore from 01-03-2022 to 30-11-2022. Methodology: One hundred and twenty three patients within 8-48 years who were suffering from acute appendicitis and required appendectomy were randomly selected. They were randomly divided into two groups. One was Diclofenac sodium group which had 61 cases in it and was selected to receive Diclofenac Sodium post-surgery. The other group having 62 patients was ketorolac group receiving ketorolac for pain relief. The patients received the pain killer post 30 and then 60 minutes after their surgery. The comparative results and efficacy of each pain killer was analyzed and assessed through faces pain scale. Results: The mean age of the patients was 20.5±5.5 in diclofenac sodium and 21.3±6.1 in Ketorolac group. There were 75.4% males in former group while 62.9% in later group. The mean value of BMI was within normal range in both groups. The pain score recorded highest number of cases in Diclofenac Sodium and ketorolac group at score 02 within 30 minutes after surgery while the pain score significantly dropped in ketorolac group in 60 minutes to score 00 while it persisted highest in score 02 among patients given Diclofenac Sodium. Conclusion: Intravenous ketorolac has advanced analgesic effect than Diclofenac Sodium with a substantial low risk involved in cases of appendectomy. Key Words: Appendicitis, NSAIDS, Ketorolac, Diclofenac, Management.